The Impact of TikTok's Live Streaming Feature on Consumer Trust Toward Online Purchases in Indonesia - Ongkowijoyo, Margareth; Hongdiyanto, Charly (Dinasti International Journal of Economics, Finance & Accounting, 2026)
The integration of live streaming and e-commerce on TikTok has transformed online shopping in Indonesia. This study investigates the impact of Utilitarian Value (functional benefits) and Hedonic Value (emotional benefits) on Continuous Purchase Intention, mediated by Trust in Product and Trust in Streamer. A quantitative approach was employed, with data collected via an online questionnaire from 202 active TikTok Shop users in Indonesia. Analysis using Partial Least Squares Structural Equation Modeling (PLS-SEM) revealed that Utilitarian Value significantly builds Trust in Product and Trust in Streamer. Hedonic Value significantly strengthens Trust in Streamer and directly influences Continuous Purchase Intention, but not Trust in Product. Both types of trust significantly drive Continuous Purchase Intention. The findings provide a trust mediation framework, highlighting that both rational and emotional elements are crucial for fostering long-term consumer loyalty on live streaming platforms. Practical implications suggest businesses should balance clear product information with entertaining content to build trust and encourage repeat purchases.